Ag/Ag3PO4 nanoparticles assembled on sepiolite nanofibers: Enhanced visible-light-driven photocatalysis and the important role of Ag decoration. (15th March 2023) - Ren, Xiaofei; Hu, Guicong; Guo, Qingbin; Gao, Dengzheng; Wang, Li; Hu, Xiaolong
Abstract: A novel visible-light-driven Ag/Ag3 PO4 /sepiolite ternary heterostructure photocatalysts were successfully prepared via a facile precipitation method. The presence of Si–OH on the surface of sepiolite converted the part of Ag  +  to Ag 0 through the in-situ reduction. the visible light degradation rate constant of Rhodamine B by Ag/Ag3 PO4 /sepiolite was about 3.68 times higher than that of bare Ag3 PO4 . The superior photocatalytic performance of Ag/Ag3 PO4 /sepiolite was attributed to the formation of Ag3 PO4 particles with smaller grain size and Ag 0 nanoparticles due to the introduction of sepiolite, resulting in the enhanced adsorption capacity, improved light response ability and accelerated photogenerated electron transfer rate. In particular, the generated Ag 0 played a very important role in improving the electron-hole separation efficiency through acting as the electron acceptor and regulating the carriers' separation path. On the other hand, the SPR effect of Ag 0 can improve the light absorption ability of the photocatalys. The radical trapping experiment showed that holes (h + ) and superoxide radical (O2 − ) were the main reactive species, where the formation of O2 − was closely related to the presence of Ag 0 . This work provides new insights for the application of hybrid photocatalysts combined with mineral materials in wastewater treatment. Graphical abstract: A novel visible-light-driven Ag/Ag3 PO4 /sepiolite ternary heterostructure photocatalysts were synthesized via a facile precipitation method. The composite exhibited the enhanced visible-light-driven acivity due to the introduction of sepiolite. This work provides new insights for the application of hybrid photocatalysts combined with mineral materials in wastewater treatment. Image 1 Highlights: Ag/Ag3 PO4 /sepiolite composite was synthesized via a facile precipitation method. Sepiolite with abundant Si–OH contributed to the formation of Ag 0 nanoparticles. The composite exhibited the improved photocatalytic activity under visible light. Potential mechanisms for enhanced visible-light-driven activity were analyzed.